Wstąpienie w stosunek najmu lokalu z mieszkaniowego zasobu gminy po śmierci najemcy na podstawie art. 691 k.c. - uwagi de lege lata i postulaty de lege ferenda - Jacko-Szcześniak, Iwona (PRAWO i WIĘŹ, 2025)
The aim of the study is to present the problematic issues that may be encountered while applying the current rules of Article 691 of the Polish Civil Code in regard to tenancy contracts of residential premises from municipal housing stock. Pursuant to current regulations of the Polish Civil Code and the Law on the Protection of Tenants’ Rights from 21st of June 2001, the entering into the tenancy contract for an indefinite period after the tenant’s death shall take place in accordance with the provisions of the Civil Code, regardless of the conditions stipulated in the Law on the Protection of Tenants’ Rights. This mechanism has raised questions of its compliance with the public interest, as the residential premises from the municipal housing stock are scarce and shall be allocated to persons with low income.